Efficacy of topical application of insulin versus platelet rich plasma versus normal saline dressings in the healing of diabetic foot ulcers: A study from a tertiary care center in India - Katiar, Vikash; Prem Shanker; Anil Kumar Verma; Mishra, Yukteshwar; Gaur, Mohini (Asian Journal of Medical Sciences, 2022)
Background: Diabetic foot ulcers (DFU) are one of the major complications of diabetes. Despite proper insulin treatment and a strict diabetic diet, 15% of diabetic population develop non-healing ulcers which leads to amputation of the lower limb. Wound dressings represent a part of the management of diabetic foot ulceration. Normal saline (0.9%) wound dressings have been a useful adjunct in the treatment of open wounds. Topical insulin dressing improves wound healing by regulating oxidative and inflammatory responses. PRP dressing has emerged as an adjunctive and newer method for treating DFUs. Hence, the present study was undertaken to compare the effect of topical insulin, platelet-rich plasma (PRP), and normal saline dressing in healing of DFU. Aims and Objectives: The aim of the study was to study the comparison between topical application of insulin versus PRP versus regular normal saline dressing in healing of DFU. Materials and Methods: It is a duration based prospective comparative study including 60 patients divided equally into normal saline dressing group, topical insulin dressing group and PRP dressing group after they fulfilled all the inclusion and exclusion criteria and after obtaining the proper informed and written consent from relatives/patients. Ulcers at days 0, 7 and 14 in terms of size, depth and percentage reduction in area of wound were analyzed. Results: The mean ulcer size at day 14 in normal saline was 4.19±0.95, in Insulin 2.64±0.83 while 2.08±0.47 in PRP group. The mean ulcer depth at day 14 in normal saline was 5.35±1.18, in insulin 4.30±1.38 while 2.35±1.42 (mm) in PRP group, percentage reduction of mean ulcer size in normal saline was 27.02±4.46, in insulin 50.31±7.53 and 63.80±5.75% in PRP group. Conclusion: PRP appears to be a promising agent in terms of faster wound healing, more significant reduction in the size of DFU as compared to topical insulin and other conventional dressings.